Mad activisms in mental health: a integrative review - Juan Carlos Cea Madrid (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
The following text presents the results of a integrative review whose purpose was to identify and analyze the production of academic literature on mad activism in the field of mental health and its link with the notions of disability and neurodiversity. From searches conducted in May 2023 in the Web of Science, Scopus, and PubMed databases, 52 articles were selected, and thematic content analysis strategies were applied. The results account for various articulations between the concepts addressed, establishing a critical look at the biomedical model in mental health. In the forms of mad activism, the human rights approach, the fight against stigma and its influence on the reform processes of the mental health system become relevant. On the other hand, a framework of social justice, identity policies and practices of mutual support from the community are established. As a whole, they emphasize methodological innovations and an intersectional perspective on the production of knowledge. It is concluded that it is possible to situate madness as a field of constitution of a political actor and epistemic subject. Based on this, possible lines of research on mad activisms in Latin America are formulated.